Cardiovascular medication and intraocular pressure: results from the Gutenberg Health Study - Höhn, René Gerhard Joachim; Mirshahi, Alireza (British journal of ophthalmology, 2017)
Background: Intraocular pressure (IOP) is well known to be associated with blood pressure and other cardiovascular risk factors. The influence of systemic cardiovascular, in particular antihypertensive, medication on IOP is still controversial. This study analyses the association between the use of cardiovascular medications and IOP in a large European cohort. Methods: The Gutenberg Health Study is a population-based, prospective,observational cohort study in mid-western Germany. IOP was measured using a non-contact tonometer. The medication classes examined were peripheral vasodilators, diuretics, β-blockers (overall, selective and non-selective), calcium channel blockers, renin-angiotensin blockers (overall, ACE inhibitors and angiotensin-receptor blockers), nitrates, other antihypertensive medications, aspirin and statins. Subjects with missing IOP values, topical IOP-lowering medication or previous ocular surgery were excluded. In total, 13 527 subjects were enrolled in this study. Association analyses between medication use and IOP were performed using multivariable linear regression (p<0.0038). Results: Neither selective nor non-selective systemic β-blocker intake was associated with statistically significant lower IOP (−0.12 mm Hg, p=0.054 and −0.70 mm Hg, p=0.037, respectively). IOP was not associated with the use of ACE inhibitors after adjustment for body mass index, systolic blood pressure and central corneal thickness (0.11 mm Hg; p=0.07). Conclusions: None of the cardiovascular medications, in particular systemic β-blocking agents, showed an association with IOP in non-glaucoma subjects. The long-term drift phenomenon of topical and systemic β-blocker might explain this result. Our results suggest that systemic β-blockers have a negligible effect on IOP reduction.